2009
DOI: 10.1103/physrevd.80.035016
|View full text |Cite
|
Sign up to set email alerts
|

Higgs mediated flavor changing neutral currents in warped extra dimensions

Abstract: In the context of a warped extra-dimension with Standard Model fields in the bulk, we obtain the general flavor structure of the Higgs couplings to fermions. These couplings will be generically misaligned with respect to the fermion mass matrix, producing large and potentially dangerous flavor changing neutral currents (FCNC's). As recently pointed out in [arXiv:0906.1542], a similar effect is expected from the point of view of a composite Higgs sector, which corresponds to a 4D theory dual to the 5D setup by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 91 publications
3
129
0
Order By: Relevance
“…mechanism [15][16][17][18]. But they can be greatly enhanced by the extended flavor structures in many new physics models, for example the minimal supersymmetric model (MSSM) with/without R-parity [19][20][21][22][23][24][25][26][27][28][29][30][31][32], two-Higgsdoublet model (2HDM) type-III [33][34][35][36][37][38][39][40][41][42][43][44][45], and the other miscellaneous models [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. So the study of top-Higgs FCNC interactions is a common interest of the theory and experiment communities [61][62][6...…”
Section: Introductionmentioning
confidence: 99%
“…mechanism [15][16][17][18]. But they can be greatly enhanced by the extended flavor structures in many new physics models, for example the minimal supersymmetric model (MSSM) with/without R-parity [19][20][21][22][23][24][25][26][27][28][29][30][31][32], two-Higgsdoublet model (2HDM) type-III [33][34][35][36][37][38][39][40][41][42][43][44][45], and the other miscellaneous models [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. So the study of top-Higgs FCNC interactions is a common interest of the theory and experiment communities [61][62][6...…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper [23], it was shown that the discrepancy between the two sets of results can be traced back to a subtlety in the calculation of the loop-induced Higgs couplings to gluons and photons. In order to compute the relevant overlap integrals of fermion wave functions with the brane-localized Higgs field, it is necessary to regularize the Higgs profile in an intermediate step and give it an infinitesimal width η [24]. When the calculation of the gluon fusion amplitude is performed in a naive way, the limits of sending the regulator to zero (η → 0) and including an infinite number of KK modes (N → ∞) in the sum over virtual states do not commute.…”
Section: Jhep01(2014)173mentioning
confidence: 99%
“…We then introduce FN messengers U c 4,3,2,1,0 , D c 4,3,2,1,0 , Q 2,1,0 plus conjugates which we labeled by their U(1) charge. In addition we have to add a certain number of JHEP08 (2011)028 these messenger fields with the same U(1) quantum numbers in order to reproduce SM masses [1][2][3][4], so that the total number of messengers with u c (d c ) SM quantum numbers is at least 12 (17). It turns out that the minimal number of additional messenger fields are two copies of D c 2,1,0 and one copy of U c 1,0 , D c 3 and Q 1,0 .…”
Section: Jhep08(2011)028mentioning
confidence: 99%